1977
DOI: 10.1093/brain/100.3.543
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the Centre Section (Trunk) of the Corpus Callosum in Man

Abstract: The case is reported of a patient in whom the middle sagittal third of the corpus callosum had been removed for the treatment of an underlying angioma. The special advantages of the case are that the patient is a young, relatively healthy person of normal IQ. The angioma had not interfered with interhemispheric transmission and the patient was described as neurologically normal before operation. After operation left-side neglect and extensive somatic disconnection were seen. A change in the balance between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 0 publications
4
19
0
Order By: Relevance
“…Finger touch localization was defective in the contralateral conditions in case 2 in our study, and similar cases have been reported previously [1, 2, 9, 11, 13, 15, 16, 17, 18]. Since these cases can localize the point being touched with the ipsilateral hand, they could be considered as having problems not in finger recognition itself but in the interhemispheric transfer of the information of touch localization.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Finger touch localization was defective in the contralateral conditions in case 2 in our study, and similar cases have been reported previously [1, 2, 9, 11, 13, 15, 16, 17, 18]. Since these cases can localize the point being touched with the ipsilateral hand, they could be considered as having problems not in finger recognition itself but in the interhemispheric transfer of the information of touch localization.…”
Section: Discussionsupporting
confidence: 89%
“…In the gross touch localization task [9], the blindfolded subject was touched on the shoulder, elbow or hand of one arm, and he/she was required to indicate, using the other hand, the point at which he/she had been touched. All cases performed well (case 1, 7/7, case 2, 10/10, and case 3, 20/20).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In surgical lesions of the corpus callosum in order to reach subcallosal tumors the splenium has always been spared. Nevertheless, a persistent anterograde memory deficit was reported both in Dimond et al's (1977) patient, and in one of the three patients studied by J eeves et al (1979) and in three of the six patients reported by Bentin et al (1984).…”
Section: Introductionmentioning
confidence: 85%